The effects of co-administration of butter on the absorption, metabolism and excretion of catechins in rats after oral administration of tea polyphenols. Issue 7 (8th July 2015) - Zhang, Liang; Han, Yuhui; Xu, Liwei; Liang, Yuhong; Chen, Xin; Li, Junsong; Wan, Xiaochun
<x xml:space="preserve">Abstract</x> A rapid UHPLC-MS/MS method was used to quantitatively determine the catechins in the plasma, feces and bile of rats after the oral administration of tea polyphenol or its combination with butter.